Effects of Symbiodiniaceae Phylotypes in Clades A–E on Progeny Performance of Two Giant Clams (Tridacna squamosa and T. crocea) During Early History Life Stages in the South China Sea - Long, Chao; Zhang, Yuehuan; Li, Yunqing; Li, Jun; Zhou, Zihua; Qin, Yanping; Li, Xingyou; Ma, Haitao; Wei, Jinkuan; Zhou, Yinyin; Noor, Zohaib; Long, Lijuan; et al. (Frontiers in Marine Science, 2021)
Unlike most bivalves, giant clams (tridacnids) harbor symbiotic microalgae (zooxanthellae) in their other fleshy bodies. The effects of mixed populations of zooxanthellae on larval metamorphosis has been reported in several papers, but there have been very few studies on the effects of single zooxanthella species on the establishment of symbiosis in giant clams. In this study, we obtained five pure zooxanthella species (clades A3, B1, C1, D1, E1) from antler coral by molecular identification, and analyzed their effects on the larval metamorphosis and progeny performance of two giant clams, Tridacna squamosa and T. crocea, in the South China Sea. Clam larvae with all five zooxanthella species underwent larval settlement and metamorphosis, and formed the zooxanthellal tubular system. There was some variation in metamorphic rate and time to metamorphosis between clams with different zooxanthella species, but no significant differences in size at metamorphosis. After metamorphosis, larvae with all zooxanthella types continued to develop normally. Mantle color was consistent within clam species and zooxanthella species had no effect on mantle color. However, clam progeny with clade E1 zooxanthellae were smaller than progeny with the other four zooxanthella clades (A3, B1, C1, and D1). Survival rate was over 90% for all progeny and there were no significant differences in survival between progeny with Symbiodinium clades A–E during the entire culture process. Two-way ANOVA analysis revealed that giant clam species was the main factor influencing progeny growth, with some variation in growth attributable to zooxanthella type. Our results provide new information on both the symbiotic relationship between giant clams and zooxanthellae and the mantle coloration of giant clams, and will be useful in giant clam seed production and aquaculture.